Evaluation of the cardiac safety of parsaclisib, a selective PI3Kδ inhibitor, in patients with previously treated B‐cell malignancies: Results from the CITADEL‐101 study - Jia Li; Xiaohua Gong; Xing Liu; Xiang Liu; Ke Szeto; Xuejun Chen (Wiley, 2024)
Abstract Parsaclisib, a potent and selective phosphatidylinositol 3 kinase δ inhibitor, has been investigated for the treatment of B‐cell malignancies and studied in patients with autoimmune diseases and myelofibrosis. The CITADEL‐101 study (NCT02018861) assessed safety, tolerability, and preliminary efficacy of parsaclisib in patients with relapsed or refractory non‐Hodgkin lymphoma. This study evaluated the cardiac safety of parsaclisib as monotherapy based on data from 72 patients enrolled in the CITADEL‐101 study. Time‐matched pharmacokinetic and ECG measurements were collected at specified times for 69 patients receiving monotherapy in doses of 5, 10, 15, 20, 30, and 45 mg once daily. Based on the categorical outlier analysis, no dose‐dependent effect was observed on the incidence of outliers in QT interval corrected for heart rate (HR) by Fridericia's method (QTcF), HR, or cardiac conduction. Based on central tendency analysis, the least square means (LSMs) (90% confidence interval [CI]) of ΔQTcF from the central tendency analysis ranged from −6.83 (−18.8 to 5.19) to 4.75 ms (0.410-9.09) across dose groups (below 20 ms, the threshold of large QT effects) and was not considered dose dependent. Moreover, the LSMs of ΔHR, ΔPR interval, and ΔQRS interval were minor. From the concentration‐ΔQTcF analyses, the predicted ΔQTcF (90% CI) for all dose levels was between 0.365 (−1.75 to 2.48) and 7.87 ms (0.921-14.8), with the highest upper limit of CIs well below 20 ms, and therefore, a large QT/QTc effect was ruled out up to the highest dose level (45 mg) investigated. Overall, parsaclisib at the dose ranges studied did not reveal concentration‐dependent effects on change in QTcF and did not have a significant effect on HR or cardiac conduction.